Virulence and antifungal susceptibility of microsatellite genotypes of Candida albicans from superficial and deep locations. Issue 5 (13th June 2019) - Wang, Meizhu; Cao, Yu; Xia, Maoning; Al‐Hatmi, Abdullah M.S.; Ou, Weizheng; Wang, Yanyan; Sibirny, Andriy A.; Zhao, Liang; Zou, Chenggang; Liao, Wanqing; Bai, Fengyan; Zhi, Xie; et al.
Abstract: A set of 185 strains of Candida albicans from patients with vulvovaginal candidiasis (VVC) and from non‐VVC clinical sources in southwest China was analysed. Strains were subjected to genotyping using CAI microsatellite typing and amplification of an intron‐containing region of the 25S rRNA gene. Microsatellite genotypes of strains from non‐VVC sources showed high polymorphism, whereas those of VVC were dominated by few, closely similar genotypes. However, among non‐VVC strains, two genotypes were particularly prevalent in patients with lung cancer. 25S rDNA genotype A was dominant in VVC sources (86.7%), whereas genotypes A, B, and C were rather evenly distributed among non‐VVC sources; known genotypes D and E were not found. In an experimental mouse model, isolates from lung cancer and AIDS patients proved to have higher virulence than VVC strains. Among 156 mice infected with C. albicans, 19 developed non‐invasive urothelial carcinoma. No correlation could be established between parameters of virulence, source of infection, and incidence of carcinoma. C. albicans strains from VVC were less susceptible to itraconazole than the strains from non‐VVC sources, whereas there was small difference in antifungal susceptibility between different 25S rDNA genotypes of C. albicans tested against amphotericin B, itraconazole, fluconazole, and flucytosine.